Building and using nonlinear simulations in Excel with an application to the specific factors model. (14th March 2023) - Gilbert, John; Koska, Onur A.; Oladi, Reza
Abstract: Excel simulation models have become increasingly common in the economics classroom, as their ability to combine numerical and graphical information has proved a useful support to traditional teaching methods. Recent efforts have tended to embed the solution within the Excel sheet, avoiding the need to use the Solver add‐in and allowing changes in the exogenous characteristics of the model to be instantly reflected in the numerical solutions and any associated geometry. While this is quite simple in small‐scale linear models, it is less straightforward in larger nonlinear models such as those that dominate the theory of international trade. We discuss various methods that can be used in building Excel simulations when it is not possible to solve the underlying model explicitly. We illustrate the ideas and describe our experiences along with a new simulation of the specific factors model.